Actual issues of studying of opisthorchiasis in Siberia - E. N. Ilyinskikh (Бюллетень сибирской медицины, 2002)
In this article it is overviewed some literature connected with the discovery and scientific description of the trematode Opisthorchis felineus more than a hundred years ago. Special attention has been paid to the relationship between opisthorchiasis and cholangiocarcinoma development in humans. Some data from research literature and the author's own publications illustrated various cytogenetic aberrations in peripheral blood lymphocytes of opisthorchiasis patients have been cited in this article. Such chromosome aberrations were detected more frequently among the new arrivals than the local inhabitants. Many of the chromosome breaks are located near to some cellular oncogenes of the human chromosomes. Superactive biotransformation of some xenobiotics into mutagenic and carcinogenic agents was found in the liver of opisthorchiasis patients. The facts about the distribution of Opisthorchis felineus in Russia are also cited.